2019
DOI: 10.1016/j.celrep.2019.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The Cardiac Microenvironment Instructs Divergent Monocyte Fates and Functions in Myocarditis

Abstract: SUMMARY Two types of monocytes, Ly6Chi and Ly6Clo, infiltrate the heart in murine experimental autoimmune myocarditis (EAM). We discovered a role for cardiac fibroblasts in facilitating monocyte-to-macrophage differentiation of both Ly6Chi and Ly6Clo cells, allowing these macrophages to perform divergent functions in myocarditis progression. During the acute phase of EAM, IL-17A is highly abundant. It signals through cardiac fibroblasts to attenuate efferocytosis of Ly6Chi monocyte-derived macrophages (MDMs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 99 publications
0
46
0
Order By: Relevance
“…Bone marrow derived circulating monocytes can differentiate into “classical” inflammatory (M1) and “non-classical” patrolling (M2) monocytes. The expression of the surface proteins CD14 and CD16 in combination with the pan-macrophage marker CD68 can be used to distinguish between these two populations [ 23 ]. However, as it was shown that the majority of heart resident human CD68 + macrophages co-express CD14 in dilated and ischemic cardiomyopathies [ 3 ], we applied CD86 and CD163 as additional markers for M1 and M2 macrophages, respectively [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone marrow derived circulating monocytes can differentiate into “classical” inflammatory (M1) and “non-classical” patrolling (M2) monocytes. The expression of the surface proteins CD14 and CD16 in combination with the pan-macrophage marker CD68 can be used to distinguish between these two populations [ 23 ]. However, as it was shown that the majority of heart resident human CD68 + macrophages co-express CD14 in dilated and ischemic cardiomyopathies [ 3 ], we applied CD86 and CD163 as additional markers for M1 and M2 macrophages, respectively [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…These bone marrow derived monocytes can differentiate to classical pro-inflammatory CD14 + CD68 + macrophages (M1 macrophages) or to non-classical immunosuppressive CD16 + CD68 + macrophages (M2 macrophages). This process is highly dependent on the cardiac microenvironment including cytokine and chemokine levels, inflammatory milieu as well as fibroblast presence [ 23 ]. Interestingly, PAI-1 has been suggested to be involved in the regulation of monocyte differentiation in cancer, as it promotes the recruitment and polarization of macrophages towards a M2 phenotype [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first monocyte population to appear is pro-inflammatory Ly6C hi monocytes which differentiate into CCR2 + macrophages. As healing proceeds, Ly6C hi monocytes gives rise to Ly6C lo monocytes which differentiate into macrophages at a lower rate and function primarily as pro-reparative cells and survey endothelial cell health for clearance [45][46][47]. The conversion and survival of Ly6C lo monocytes is controlled by Nuclear receptor subfamily 4 group A member 1 (Nr4a1, aka Nur77) [48,49].…”
Section: Myeloid Cell Activity After Myocardial Infarctionmentioning
confidence: 99%
“…There is estimated around 20% of patients with myocarditis developing dilated cardiomyopathy (DCM) [92]. Studies indicate that different regulations of monocyte differentiation involve in the cardiac microenvironment of myocarditis patients [93]. Given the autoimmune myocarditis animal model and clinical observations, monocytes and macrophages represent around 75% of migrating cells surrounding the injured myocardium [94].…”
Section: Gsk3β Modulation In Dilated Cardiomyopathymentioning
confidence: 99%
“…A recent study indicated that IL-17 and HMGB1 could aggravate the cardiomyocyte apoptosis and autophagy. Extracellular HMGB1 was reported to cause cardiac remodeling, hypertrophy, reperfusion injury and myocardial fibrosis [92,93]. Since autophagy is regulated by autophagy-related proteins, such as, LC3-II/LC3-I and Beclin-1 [105], the increased ratio of LC3-II to LC3-I and the Beclin-1 expression are of significance in H/R group.…”
Section: Gsk3β Modulation In Dilated Cardiomyopathymentioning
confidence: 99%